INDUCTION OF DEFENSE ENZYMES IN FLOURESCENT PSEUDOMONADS AGAISNT WILT COPMLEX PATHOGENS OF MEDICINAL PLANTS - S. B. MALLESH; S. LINGARAJU (The Bioscan, 2015)
The efficacy of seven potential fluorescent pseudomonads from different parts of Karnataka were tested for the induction of systemic resistance against wilt complex in two medicinal plants (coleus and ashwagandha) caused by Fusarium sp., Ralstonia solanacearum and Meloidogyne incognita. Among seven isolates of fluorescent pseudomonads, RB-50 and RB-31were enhanced the plant growth parameters with >85% germination and highest vigour index of 753.87 in ashwagandha. The highest number of branches and tubers per plant in coleus were observed in RB50 (13.33 and 10.33) followed by RB31 (11.00 and 8.00) respectively. Induced systemic resistance through as inferred biochemical analysis revealed the increased activities of the enzymes, viz. peroxidase (PO), polyphenol oxidase (PPO), phenylalamine ammonia lyase (PAL) and also phenolic compounds in the PGPR treated plants of coleus and ashwagandha challenged with individual and combinations of their pathogens. The increase in production, expression of defense enzymes and other compounds in PGPR treated plants upon challenge inoculation with different pathogens were comparatively higher when compared to uninoculated control. The observation revealed that, RB-50 and RB-31 fluourescent pseudomonads isolates were found effective, systemically induced resistance against wilt complex pathogens of coleus and ashwagandha by the accumulation of battery of enzymes in response to pathogens infection.